Perspektif Karyawan Perbankan pada Komunikasi Internal dengan Two-Way Symmetrical Communication dan Internal Marketing - Angeline, Mia (Humaniora, 2013)
The article investigates the internal communication in the two branches of foreign banks in Kelapa Gading from the perspectives of two-way symmetrical communication and internal marketing. The second problem investigated is the effectiveness of the use of email as a means of internal communication. Data were collected through interviews and literature. The results showed that the perception of employees not in accordance with the concept of two-way communication and internal marketing, but this policy has led the organization to these concepts. In the use of email, employee perceptions still see that the email is an effective internal communication media despite having many weaknesses.